Analisis Variasi Bahasa pada Pelayanan Rumah Sakit Umum Daerah Kotabaru - Husni Mubarak (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2020)
The purpose of this study was (1) to describe the variations in language contained in the service at the Kotabaru Regency General Hospital, (2) to describe the factors of language variation found in the service of the Kotabaru Regency Regional General Hospital. The method used in this study is a qualitative method that is descriptive by describing objectively and the actual speech that occurs. While this type of research is a qualitative descriptive study with analyzing data through field observations with the steps of collecting, analyzing and presenting data with observation techniques, recording techniques and note taking techniques. Based on the results of research conducted, it was found that variations in the language used by doctors, nurses, and patients were three language variations namely 1. language variation in terms of facilities, namely variations or variations in spoken language; 2. variations in language based on usage terms, namely variations in language functions or registers, and 3. variations in language based on the degree of officiality are variations in business languages ​​or variations in business, variations in casual languages ​​(casual). And the factors of language variation in the services of the Kotabaru District General Hospital are situational factors, gender factors, occupational or professional factors, environmental factors and educational factors. Keywords: Language Variation, Regional General Hospital Services